Behind the Myth: The Representation of the Crimean War in Nineteenth-century British Newspapers, Government Archives & Contemporary Records - Tri Tran (Cahiers Victoriens et Edouardiens)
The objective of this contribution is to analyse the discrepancies between different contemporary sources (the national press, government papers and some individuals’ accounts) regarding the representation of the Crimean war. It appears that the representation of this war changed considerably between 1854 and 1856: it was overall fairly misleading and partial. The national press and the public opinion were too optimistic although the British government and the army were largely unprepared for this major operation. The representation of the war was misleading because the government tried to cover up the incompetence of some senior officers and the disorganization of the army administration. The poor condition of British servicemen and the hazardous nature of the Crimean venture were revealed by press reports and individuals’ accounts. In the end prominent historians consider the Crimean war was in many aspects useless and costly; the argument of this paper is that painful historical truth came to be hidden in the depth of Britain’s national consciousness, behind a few comforting Victorian myths.